Феномен золотих "лихоманок" як територіальне, гірниче й соціокультурне освоєння Північної Азії (Частина третя) - Гайко, Геннадій Іванович; Білецький, Володимир Стефанович (Український культурологічний центр, 2017)
У циклі статей систематизовано події заселення та економічного освоєння величезних просторів Північної Америки, Австралії, Південної Африки, Північної Азії, що пов'язані з рухом шукачів золота й алмазів (золотими й алмазними "лихоманками"). Наведено хронологічний огляд подій, дано аналіз загальному феномену явища, розкриті особливості його історичної, гірничо-геологічної й організаційної складових. Матеріал розділено на три окремі, але тематично поєднані частини, що описують явище "золотої лихоманки" - стихійного масового видобування золота на нововідкритих родовищах у другій половині ХІХ - на початку ХХ ст. у віддалених (для європейців) частинах світу. Автори висвітлюють події в Північній Азії - на Уралі та в Сибіру.

This series of articles systematizes the events of settlement and economic development of vast spaces of North America, Australia, South Africa and North Asia, which are related to the movement of gold and diamond hunters (gold and diamond rushes). A chronological survey of the events is offered, the general phenomenon analyzed as well as specific aspects of its historical, mining, geological and organizational constituents covered. The material is divided into three separate but thematically united parts which describe the phenomenon of gold rush-spontaneous large-scale gold mining at newly discovered deposits in remote (for Europeans) parts of the world in the second half of the 19th century - the early 20th century. The impact of gold rushes in North America and Australia on the processes of global economic and financial transformations is shown. Large outputs resulted in setting a monetary gold standard which had been in place up to World War I: a wide turnover of gold coins, displacement of silver which began to act as token money as well as free exchange of paper money for gold coins. The above contributed to a sustainable development of world money relations which gave rise to a global financial system in the modern sense; a significant banks' influence on economic transformations as well as establishment of international centers for financial capital. Huge gold reserves were purposefully accumulated in the USA which, extracting an ample quantity of gold in its territory, bought up a considerable part of the world gold output, which eventually secured the key status of the American currency in world trade. Extracted gold played a key role in provision of financial resources for large-scale industrial development of the industrial epoch. Numerous migrations of working people from gold mining sites promoted the development and settlement of remote territories as well as the utilization of their natural resources in the global economic development.
Phenomenon of gold rushes as territorial, mining and socio-cultural development of North Asia (Part III)
Keywords: старателі; шліховий метод; розсипи; жильне золото; Урал; Сибір; мінеральні ресурси; гірництво; golden fever; scavengers; leaching method; placers; housing gold; North Asia; Ural; Siberia